Operation of nutrient removal facilities : WEF manual of practice no. 37. (Water Environment Federatiion, 2013)
Annotation This manual is ideal for plant managers, operators, design engineers, and regulators looking to gain a better understanding of fundamental biological and chemical processes that are in use at nutrient removal facilities and the ways that operators may use, monitor, and control these processes to meet their facility's treatment goal. Table of contents Chapter 1: Introduction Chapter 2: Wastewater Constituents that Affect Nutrient Removal Chapter 3: Nitrification Chapter 4: Nitrification in Biofilm Reactors Chapter 5: Denitrification Chapter 6: Combined Nitrifying and Denitrifying Systems Chapter 7: Enhanced Biological Phosphorus Removal Chapter 8: Chemical Precipitation of Phosphorus Chapter 9: Enhanced Biological Phosphorus Removal Systems Chapter 10: Combined Nitrogen and Phosphorus Removal Processes Chapter 11: Optimization of Nutrient Removal Systems Chapter 12: Recycle Streams Management Chapter 13: Process Control Using Oxidation-Reduction Potential and Dissolved Oxygen Chapter 14: Process Control, Instrumentation, and Automation Chapter 15: Laboratory Analyses Chapter 16: Case Studies-Nitrification and Denitrification Chapter 17: Case Studies-Enhanced Biological Phosphorus Removal Appendix A Optimization and Troubleshooting Guides This book was prepared by the Operation of Nutrient Removal Facilities Task Force of the Water Environment Federation.
Includes index.
Keywords: Sewage -- Purification -- Aeration.; Sewage lagoons.; Sewage disposal plants.; elektronické knihy; electronic books